Antibiotic resistance of Pseudomonas aeruginosa isolated from hospital wastewater in the Czech Republic. (12th April 2022) - Roulová, Nikola; Mot'ková, Petra; Brožková, Iveta; Pejchalová, Marcela
Abstract: Resistant bacteria may leave the hospital environment through wastewater. The opportunistic pathogen Pseudomonas aeruginosa, due to its intrinsic resistance to many antibiotics and its ability to easily acquire antibiotic resistance determinants, poses a significant threat to public health. The aim of this study was to evaluate the antibiotic resistance profiles of cultivated P. aeruginosa in untreated hospital effluents in the Czech Republic. Fifty-nine P. aeruginosa strains isolated from six hospital wastewaters were tested for antimicrobial susceptibility through the disc diffusion method against seven antimicrobial agents. Resistance was found in all antibiotics tested. The highest resistance values were observed for ciprofloxacin (30.5%), gentamicin (28.8%), and meropenem (27.2%). The P. aeruginosa isolates also exhibited resistance to ceftazidime (11.5%), amikacin (11.5%), piperacillin-tazobactam (11.5%), and aztreonam (8.5%). Seventeen strains of P. aeruginosa (28.8%) were classified as multidrug-resistant (MDR). The results of this study revealed that antibiotic-resistant strains are commonly present in hospital wastewater and are resistant to clinically relevant antipseudomonal drugs. In the absence of an appropriate treatment process for hospital wastewater, resistant bacteria are released directly into public sewer networks, where they can serve as potential vectors for the spread of antibiotic resistance. HIGHLIGHTS: Pseudomonas aeruginosa is commonly present in untreated hospital wastewater. The isolates presented resistance to clinically relevant antipseudomonal drugs. 28.8% of P. aeruginosa strains were identified as multidrug-resistant (MDR). Resistant strains are released with untreated hospital effluents into public sewer networks where antibiotic-resistant strains can easily spread. Graphical Abstract